Indonesia’s Dynamic Electricity Power Sector: Investigating Need and Supply Performance - Latif Adam; Maxensius Tri Sambodo (Institute for Economic and Social Research, 2015)
This paper analyzes the development and problems of electricity sector in Indonesia. After the economic crisis of 1997/98, investment in power sector has been decreasing. Minimizing transmission and distribution loss can increase reliability and quality of power supply, improve financial capacity, and reduce electricity subsidy. Electrification ratio and electric power consumption per capita need to be improved equally among provinces. Promoting public private partnership (PPP) can boost investment. Main policy challenges need to be addressed are that government needs to (1) provide information on the investment prospects; (2) solve social aspect of the project; and (3) provide practical guide in land acquisition.